Developing and Testing Twelve-Step Facilitation for Adolescents with Substance Use Disorder: Manual Development and Preliminary Outcomes - John F. Kelly; Julie D. Yeterian; Julie V. Cristello; Yifrah Kaminer; Christopher W. Kahler; Christine Timko (SAGE Publishing, 2016)
Adolescent substance use disorder treatment programs are often based on the 12-step philosophy of Alcoholics Anonymous and/or link adolescents to these free resources. Despite this, no studies have developed and rigorously tested a twelve-step facilitation (TSF) intervention for young people, leaving a significant evidence gap. This study describes the first systematic development of an outpatient adolescent TSF treatment. An integrated twelve-step facilitation (iTSF) treatment incorporated TSF, motivational enhancement therapy, and cognitive behavioral therapy elements and was developed in an iterative manner with weekly feedback provided by 36 adolescents ( M age 17 years [SD = 1.4]; 52.8% white) with DSM-IV substance use disorder recruited from the community. Assessments were conducted at baseline and at three and six months. Participants completed 6 of 10 sessions on average (8 participants completed all 10). Notable treatment developments were the inclusion of "in-services" led by Marijuana Anonymous members, including parents in a portion of individual sessions to provide a rationale for TSF, and use of a Socratic therapeutic interaction style. Acceptability and feasibility of the treatment were excellent (treatment satisfaction was 4.29 [SD = 0.59] out of 5). In keeping with TSF theory, the intervention substantially increased 12-step participation, and greater participation related to greater abstinence. iTSF is a replicable manualized treatment that can be implemented and tested in outpatient settings. Given the widespread compatibility of iTSF with the current adolescent treatment, if found efficacious, iTSF could be relatively easily adopted, implemented, and sustained and could provide an evidence-based option that could undergird current practice.